DEVELOPING STUDENTS' LOGICAL THINKING IN MOTHER TONGUE CLASSES - Omonillayeva Makhfuza; Turdimurodova Shodiya (Western European Studies, 2024)
In this article, instructions and opinions on developing students' logical thinking, correct reasoning, ability to converse on any topic and fluent speaking skills are expressed in mother tongue classes.
Keywords: Mother tongue; thinking; riddle; puzzle